2019
DOI: 10.1051/0004-6361/201936750
|View full text |Cite
|
Sign up to set email alerts
|

Multiple nitrogen reservoirs in a protoplanetary disk at the epoch of comet and giant planet formation

Abstract: The isotopic ratio of nitrogen measured in primitive Solar System bodies shows a broad range of values, the origin of which remains unknown. One key question is whether these isotopic reservoirs of nitrogen predate the comet formation stage or are posterior to it. Another central question is elucidating the processes that can produce the observed variations in the 14 N/ 15 N isotopic ratio. Disks that orbit pre-main-sequence (TTauri) stars provide unique opportunities for observing the chemical content of anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 30 publications
(45 reference statements)
6
22
0
Order By: Relevance
“…Still, for the one disk with spatially resolved emission (V4046 Sgr), an increasing HCN/HC 15 N ratio moving outwards in the disk suggests that in situ photodissociation-driven fractionation is important. A similar result is seen in the TW Hya disk by Hily-Blant et al (2019). Measurements of D and 15 N fractionation in HCN towards Class 0/I disks are still needed to evaluate whether younger disks demonstrate similar fractionation patterns, or if there is a distinct Class II fractionation chemistry.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…Still, for the one disk with spatially resolved emission (V4046 Sgr), an increasing HCN/HC 15 N ratio moving outwards in the disk suggests that in situ photodissociation-driven fractionation is important. A similar result is seen in the TW Hya disk by Hily-Blant et al (2019). Measurements of D and 15 N fractionation in HCN towards Class 0/I disks are still needed to evaluate whether younger disks demonstrate similar fractionation patterns, or if there is a distinct Class II fractionation chemistry.…”
Section: Introductionsupporting
confidence: 63%
“…We note that 13 C fractionation is not expected to be important for HCN in protostellar or disk environments (e.g. Roberts et al 2002;Hily-Blant et al 2019). For J1609, J1612, and J1614, C 18 O column densities are found from 13 CO assuming the local ISM 16 O/ 18 O ratio of 560±25 (Wilson & Rood 1994) and the same 12 C/ 13 C ratio as before.…”
Section: Hcn C 2 H and C 18 O Correlations Across Evolutionary Stagessupporting
confidence: 49%
See 2 more Smart Citations
“…One is isotope-selective photodissociation of N 2 (Heays et al 2014(Heays et al , 2017, which is expected to be effective in environments where UV radiation has a significant impact on chemistry, such as the upper layers of protoplanetary disks. A recent measurement of the 14 N: 15 N ratio in the CN and HCN molecules in the circumstellar disk of the 8 Myr-old T Tauri object TW Hya demonstrated that the HCN:HC 15 N ratio increases with distance from the central star (Hily-Blant et al 2019). This observational result lends support to the hypothesis that selective photodissociation of N 2 (Heays et al 2014) could be the leading fractionation process in such disks.…”
Section: Introductionmentioning
confidence: 58%